Men Fear Other Men Most: Gender Specific Brain Activations in Perceiving Threat from Dynamic Faces and Bodies – An fMRI Study - Kret, Mariska E.; Pichon, Swann; Grezes, Julie; De Gelder, Beatrice (Frontiers in Psychology, 2011)
Gender differences are an important factor regulating daily interactions. Using functional magnetic resonance imaging (fMRI) we show that areas involved in processing social signals are activated differently by threatening signals send from male or female facial and bodily expressions and these activity patterns are different for male and female participants. Male participants pay more attention to the female face as shown by increased amygdala activity. But a host of other areas indicate a selective sensitivity for male observers attending to male bodily expressions (extrastriate body area, superior temporal sulcus, fusiform gyrus, pre-supplementary motor area and premotor cortex). This is the first study investigating gender differences in processing dynamic female and male facial and bodily expressions and it illustrates the importance of gender differences in affective communication.